2009
DOI: 10.1155/2009/747803
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Sensors Based on Photonic Crystal Fiber Modal Interferometers

Abstract: We review the research on photonic crystal fiber modal interferometers with emphasis placed on the characteristics that make them attractive for different sensing applications. The fabrication of such interferometers is carried out with different post-processing techniques such as grating inscription, tapering or cleaving, and splicing. In general photonic crystal fiber interferometers exhibit low thermal sensitivity while their applications range from sensing strain or temperature to refractive index and vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…A few authors have reported interferometric [10] and polarimetric sensors [11] embedded in composite materials. What has not been well examined in the previous research studies is the impact of the characteristic properties of the composite materials and also the effect of the fiber buffer coating on the characteristics of the embedded fiber sensors.…”
Section: Introductionmentioning
confidence: 99%
“…A few authors have reported interferometric [10] and polarimetric sensors [11] embedded in composite materials. What has not been well examined in the previous research studies is the impact of the characteristic properties of the composite materials and also the effect of the fiber buffer coating on the characteristics of the embedded fiber sensors.…”
Section: Introductionmentioning
confidence: 99%
“…More cladding modes will also be excited and when the interference spectra were Fourier transformed, multiple spatial frequencies were seen with the number increasing with increasing interferometer length [22]. Different lengths of PCF were studied and compared for sensitivity [23][24][25]. It was found that the sensitivity was not strongly dependent on length, though longer sections could require better handling and packaging.…”
Section: Mach-zehnder Interferometer (Mzi)mentioning
confidence: 99%
“…Compared with a standard single mode fiber MZI, Ju et al [47] were able to obtain a higher strain sensitivity (À2.6 pm/με compared to +0.445 pm/με) and a lower temperature sensitivity (42.4 pm/ C per m compared to 1215.56 pm/ C per m). MZIs made with LPGs can be at risk of having a high insertion loss [24] due the deformation of fiber structure from inscription or from the misaligned splice point [45]. By cascading an LPG with a PCF MZI, simultaneous temperature and RI sensing was achieved as both elements in the sensor matrix responded differently to the multiple parameters [48].…”
Section: Mach-zehnder Interferometer (Mzi)mentioning
confidence: 99%
“…The period or fringe spacing of these interferometers is (1) being the effective refractive index difference between the modes participating in the interference [13].…”
Section: Mzi Surrounded By Lcmentioning
confidence: 99%